The Collaboration of Teaching at The Right Level Approach with Problem-Based Learning Model - Mustafa Sriyanti; Riana Rika; Baharullah Baharullah; Maming Khadijah (De Gruyter, 2024)
This study aims to explore the effectiveness of collaboration between the Teaching at the Right Level (TaRL) approach and the problem-based learning (PBL) model in improving student learning outcomes at junior high school and senior high school levels. TaRL is a method that emphasizes learning tailored to students' individual ability levels, while PBL focuses on PBL that encourages students to develop critical thinking and problem-solving skills independently. In this study, 73 students participated in two cycles of learning practices integrating the two approaches. The results of the initial diagnostic test were used to group students based on their ability levels, which were then followed by the implementation of learning using problem-based scenarios according to their groups. Quantitative data were obtained through learning outcome tests and analyzed using descriptive statistics and ANOVA. The mean value of students' final test results reached 79.73, indicating a significant increase in understanding after the implementation of this method. However, the ANOVA results showed that there was no significant difference between the tested groups, with a p-value of 0.662 and an F-statistic of 0.414. In addition, in-depth interviews were conducted to understand students' perceptions of the applied learning method. The results of the interviews revealed that students felt more engaged and motivated in the learning process, especially since the materials were tailored to their abilities and they were given the opportunity to solve problems relevant to real life. However, variations in learning outcomes were still evident, indicating the need for further adjustments in the approach to reduce performance disparities between students. This study concludes that the collaboration of TaRL and PBL can be an effective strategy for improving learning outcomes. However, adaptation and continuous monitoring are needed to ensure that all students can benefit the most from this approach.